Impact of English Language Proficiency on the Job Grabbing Process of Engineers in Nepal and the Other Countries: A Bird's Eye View - Shrestha, Rup Narayan; Awasthi, Jai Raj; Pahari, Bharat Raj (Journal of the Institute of Engineering, 2018)
This paper presents the findings of a research carried out on the impact of English language proficiency on the job grabbing process of the engineers in Nepal and a few other countries. Based mainly on the review of literature that were available in the internet websites, this paper sheds light on the facts that the English language proficiency is extremely important for the global engineers today. It reveals that the ability to communicate in English efficiently in their workplace is of paramount importance for engineers not only in Nepal but also in the other countries. In the present day context, the employers want to hire merely those candidates who possess sufficient proficiency in English. Journal of the Institute of Engineering, 2018, 14(1): 223-234